Genotype-specific detection of Giardia lamblia in stool samples of diarrhoeal and non-diarrhoeal patients in Dhaka, Bangladesh - Alam, Md Masud; Ilias, Mohammad; Siddique, Md Abdullah; Kabir, Md Mamun; Nazib, Farida; Musawwir Khan, Md Gulam (Dhaka University Journal of Biological Sciences, 2011)
Two major genotypic assemblages (A and B) of Giardia lamblia infect humans. A single-vessel multiplex real-time PCR assay was used that genotypes Giardia infections into assemblages A and/or B directly from fecal samples. In this study, 157 diarrhoeal (symptomatic) and non-diarrhoeal (asymptomatic) stool samples collected from the International Centre for Diarrhoeal Disease Research, Bangladesh (ICDDR,B) and Bangabandhu Sheikh Mujib Medical University (BSMMU) hospital, respectively were analyzed to determine whether an association exists between infections with G. lamblia assemblages A or B and diarrhea in Bangladesh. Of the 157 stool samples, Giardia cysts were observed in 35 by microscopy and 127 showed positive result for Giardia cyst specific antigen. The 127 ELISA positive samples were assayed for genotyping by real?time polymerase chain reaction. Of the 117 real-time PCR positive stool samples, 15 were positive for G. lamblia assemblage A, 96 were positive for assemblage B and 6 samples showed positive result for both G. lamblia assemblage A and B infections. Higher ratios for diarrhea were observed for assemblage A infections, whereas higher parasite DNA loads and a higher overall rate were observed for assemblage B infections in both diarrhoeal and non-diarrhoeal patients. Real-time PCR is, therefore, useful as an additional test supplementary to microscopy or enzyme immunoassay to detect genotypes of Giardia. Key words: Giardia lamblia; Genotypes; Multiplex real-time PCR; Immunoassay DOI: http://dx.doi.org/10.3329/dujbs.v20i2.8979 DUJBS 2011; 20(2): 183-189